Formulasi dan Karakterisasi Nanokomposit Polyvinyl alkohol-Na CMC dengan Penambahan Antibiotik Ciprofloxacin sebagai Balutan Luka Wound Dressing - Annisa, Nabilah Shafa; Imanto, Teguh (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Ineffective wound care and bacterial infections are among the major barriers to optimal wound healing. Conventional wound dressing often fail to maintain proper moisture and lack antimicrobial activity, requiring the development of more advanced alternatives. Objective: This study aimed to develop and evaluate a modern nanocomposite-based wound dressing system combining PVA, Na-CMC, and ciprofloxacin as a local antibacterial agent. Methods: Nanocomposite films were formulated using polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (Na-CMC), and ciprofloxacin. Three formulas were developed with varying concentrations of PVA and Na-CMC. The formulations were evaluated through surface morphology analysis using Scanning Electron Microscopy (SEM), swelling test, biodegradation, mechanical strength, antibacterial activity against Staphylococcus aureus, and ciprofloxacin entrapment efficiency. Results: The formula with the highest Na-CMC content showed the best performance, with the largest pore size (52.74 nm), the highest swelling ratio (432.13%), the widest inhibition zone (3.65 ± 0.05 mm), and the highest entrapment efficiency of ciprofloxacin (91.95%). Conclusion: The developed nanocomposite film exhibits favorable physical and biological characteristics, supporting its potential use as a modern wound dressing to accelerate healing and prevent bacterial infections.